Characteristics of Arabic Language Learning in Indonesia Era 4.0 - Baiq Intan Afrianingsih; Naifah; Nur Laila Azizah; Siti Sanah; Muhammad Athif Audl Ramadlan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Arabic language learning in Indonesia has undergone a significant transformation in the era of industrial revolution 4.0. Based on technological developments and changes in learner behavior, the background of this research includes several things, such as the development of digital technology that affects learning methods, changes in learner behavior that are more likely to be digital-native, continuous development of learning media, and the need for learning that is relevant to global developments and integration with other fields. This research aims to comprehensively examine the characteristics of Arabic language learning in the context of the digital era. The type of research used is a literature study. This research identifies subsections of Arabic language learning that are relevant to the use of technology. The research participants consisted of various written sources such as books, journals, and scientific articles that discuss Arabic language learning in the digital era. This method updates previous findings and identifies new trends in Arabic language learning. The research design used is descriptive qualitative, which allows the researcher to describe the characteristics and dynamics of Arabic language learning in depth. The results show some of the main characteristics of Arabic language learning in the 4.0 era, including: (1) Intensive use of technology, including mobile learning applications, e-learning platforms, and multimedia; (2) Curriculum adaptation that integrates 21st century skills and prepares students for global challenges; (3) Innovation of learning methods such as blended learning and adaptive learning; (4) Development of interactive digital learning media; and (5) Changes in the evaluation system towards computer-based assessment and authentic assessment. Although this transformation opens up new opportunities in Arabic language teaching, there are challenges such as the digital divide and the readiness of educators that need to be addressed. This study concludes that the characteristics of Arabic language learning in the 4.0 era show a shift towards a more dynamic and technology-based approach, but still emphasize the importance of integrating cultural values and local wisdom in the educational process. This research contributes significantly to mapping the landscape of Arabic language learning in the digital era. However, there are ample opportunities for further research, especially in the aspects of evaluating the effectiveness of media use, developing more focused learning models, and exploring and applying the latest technology. It is also hoped that future research will use a more diverse sample, covering various backgrounds and age groups, so as to produce more comprehensive findings on the development of Arabic language learning along with technological advances.